2022
DOI: 10.7759/cureus.21322
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasound-Guided Serratus Anterior Plane Block for Managing Pain Due to Multiple Rib Fractures: A Scoping Review

Abstract: Ultrasound (US) guided serratus anterior plane block (SAPB) is a fascial plane block that has been utilized for managing pain after thoracotomy, mastectomy, and fractured ribs. We conducted this qualitative review to investigate the analgesic efficacy of US-guided SAPB in patients who sustained multiple rib fractures (MRFs).We registered our review proposal in a prospective register of systematic reviews, PROSPERO, with identifier CRD42020177145. This review adheres to Preferred Reporting Items for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The authors concluded that there is no difference in efficacy between the SAPB and PVB and epidural anesthesia but noted that the SAPB is a technically easier procedure with more flexibility in patient positioning and fewer contraindications. Nair and Diwan 51 conducted a qualitative review of the literature on the SAPB. In total, 16 articles in total were used in this review concluding that the continuous SAPB was found to be favorable to the single injection method when left in the patient for 3 to 5 days.…”
Section: Other Invasive Analgesic Proceduresmentioning
confidence: 99%
“…The authors concluded that there is no difference in efficacy between the SAPB and PVB and epidural anesthesia but noted that the SAPB is a technically easier procedure with more flexibility in patient positioning and fewer contraindications. Nair and Diwan 51 conducted a qualitative review of the literature on the SAPB. In total, 16 articles in total were used in this review concluding that the continuous SAPB was found to be favorable to the single injection method when left in the patient for 3 to 5 days.…”
Section: Other Invasive Analgesic Proceduresmentioning
confidence: 99%
“…This technique, injecting a certain concentration and volume of non-opioid analgesics into the surface of the anterior serratus muscle or deep interstitial space by a simple operation, confers a more complete and wider nerve block effect and has less complications [ 15 ]. SAPB has shown good performance on postoperative pain management and reducing postoperative opioid consumption in thoracotomy, breast surgery and rib fracture surgery [ 16 18 ]. Thus, SAPB appears to be an effective and safe region block that is easy to perform.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The efficacy of these regional blocks has also been demonstrated in the management of rib fractures. 7,8 A recent systematic review of nerve blocks in plastic surgery has shown favorable outcomes. 9 Of the known truncal regional blocks, PEC 1 and SAP are the least studied, and currently there is no medical evidence which demonstrates their superiority over blind local infiltration anesthesia in plastic surgery.…”
mentioning
confidence: 99%
“…PECs and SAP regional blocks are newer regional anesthetic techniques that have shown efficacy in specialties other than plastic surgery and have become part of routine management for patients undergoing a variety of procedures, including mastectomy, breast lumpectomy, video-assisted thoracic surgery, and others 1–6 . The efficacy of these regional blocks has also been demonstrated in the management of rib fractures 7,8 . A recent systematic review of nerve blocks in plastic surgery has shown favorable outcomes 9 .…”
mentioning
confidence: 99%